HUBUNGAN PENGETAHUAN DAN POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN SOSIAL ANAK DENGAN RETARDASI MENTAL DI MALUKU TENGAH - Vernando Yanry Lameky; Mevy Lilipory; Clemen Halalohun (Pattimura University, 2022)
Mental retardation is a general decline in intellectual function that occurs during childhood development and is associated with impaired social adaptation. The purpose of this study was to determine the relationship between knowledge and parenting styles of parents on the social development of children with mental retardation. The research method is descriptive with a cross sectional approach. The data collection technique used a total sampling of 44 respondents. Data were collected using a questionnaire and the Vienland Social Maturity Scale (VSMS). Data analysis used Chi-Square nonparametric statistical analysis. The results of the Chi-square test showed that the p-value = 0.039 (p≤0.05) for parents' knowledge of children's social development and p-value = 0.012 (p≤0.05) for parenting styles on children's social development. The conclusion of the study is that there is a significant relationship between knowledge and parenting styles of parents on the social development of children with mental retardation. Keywords: knowledge; social development; parenting; mental retardation